THE EFFECTIVENESS OF SOCIAL MEDIA MARKETING IN INCREASING SALES OF LOCAL PRODUCTS - Magdalena Depriyani; Al-Amin Al-Amin (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to determine the Effectiveness of Social Media Marketing in Increasing Local Product Sales. The research method in this study uses a descriptive qualitative approach. The research subject: 10 MSME actors engaged in the food, handicrafts, and fashion sectors. Data collection techniques: in-depth interviews, observation of the use of social media accounts (Instagram, TikTok, Facebook), and documentation of posts or advertisements. The results of this study show that social media marketing has proven to be effective in increasing sales of local products through increasing engagement, sales conversion, and expanding consumer reach. Social media provides an excellent opportunity for MSMEs to promote products cost-effectively but with a broad impact.